A near-infrared fluorescence probe for imaging of pantetheinase in cells and mice in vivo. Issue 47 (2nd October 2020) - Yang, Yuantao; Hu, Yiming; Shi, Wen; Ma, Huimin
Abstract : A near-infrared fluorescence probe for detecting pantetheinase activity has been used for imaging pantetheinase in mice with inflammatory bowel disease. Abstract : Pantetheinase is an amidohydrolase that cleaves pantetheine into pantothenic acid and cysteamine. Functional studies have found that ubiquitous expression of this enzyme is associated with many inflammatory diseases. However, the lack of near-infrared fluorescence probes limits the better understanding of the functions of the enzyme. In this work, we have developed a new near-infrared fluorescence probe, CYLP, for bioimaging of pantetheinase by using pantothenic acid with a self-immolative linker as a recognition group. The probe produces a sensitive fluorescence off–on response at 710 nm to pantetheinase with a detection limit of 0.02 ng mL −1 and can be used to image the intraperitoneal pantetheinase activity in mice in vivo . Moreover, with the probe we have observed that pantetheinase is significantly increased in the tissues of mouse inflammatory models as well as in the intestines of mice with inflammatory bowel disease. Therefore, CYLP may provide a convenient and intuitive tool for studying the role of pantetheinase in diseases.